2020
DOI: 10.1093/ajcn/nqaa266
|View full text |Cite
|
Sign up to set email alerts
|

Association between diet and periodontitis: a cross-sectional study of 10,000 NHANES participants

Abstract: Background Periodontitis is a major cause of tooth loss globally. Risk factors include age, smoking, and diabetes. Intake of specific nutrients has been associated with periodontitis risk but there has been little research into the influence of overall diet, potentially more relevant when formulating dietary recommendations. Objectives We aimed to investigate potential associations between diet and periodontitis using novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 30 publications
3
47
1
Order By: Relevance
“…In contrast, an anti‐inflammatory pattern is characterized by frequent intake of vegetables and fruits, whole grains, legumes, nuts, and fish (Ahluwalia et al, 2013). Using a data‐driven approach in the NHANES population, the dietary pattern (rich in salad, fruit and vegetables, poultry, and seafood) was negatively associated with the extent of periodontitis (Wright et al, 2020). These epidemiological studies reported that periodontal status might be affected by inflammatory eating patterns defined using principal components analysis (Alhassani et al, 2021) and treelet transformation analysis (Wright et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, an anti‐inflammatory pattern is characterized by frequent intake of vegetables and fruits, whole grains, legumes, nuts, and fish (Ahluwalia et al, 2013). Using a data‐driven approach in the NHANES population, the dietary pattern (rich in salad, fruit and vegetables, poultry, and seafood) was negatively associated with the extent of periodontitis (Wright et al, 2020). These epidemiological studies reported that periodontal status might be affected by inflammatory eating patterns defined using principal components analysis (Alhassani et al, 2021) and treelet transformation analysis (Wright et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Using a data‐driven approach in the NHANES population, the dietary pattern (rich in salad, fruit and vegetables, poultry, and seafood) was negatively associated with the extent of periodontitis (Wright et al, 2020). These epidemiological studies reported that periodontal status might be affected by inflammatory eating patterns defined using principal components analysis (Alhassani et al, 2021) and treelet transformation analysis (Wright et al, 2020). Both analyses derive a summary score for each pattern through statistical modelling of dietary data at hand (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been argued that a so-called industrialized western diet rich in processed carbohydrates like sugar, white flour, and processed fatty acids like trans fats and poor in micronutrients promotes gingival and periodontal inflammation (Woelber and Tennert, 2020 ). A cross-sectional study in 10,000 participants in the NHANES cohort, on the other hand, revealed the effects of a protective diet (Wright et al, 2020 ). In some instances, associations have been also revealed with factors such as the composition of the oral microbiota (Jockel-Schneider et al, 2021 ; Li et al, 2021 ).…”
Section: Medical Aspects Of Periodontal Inflammationmentioning
confidence: 99%
“…Although the mechanism is not fully understood, diet has been reported to be significantly associated with periodontitis, 9‐13 with healthier dietary patterns or better diet quality having a protective effect on periodontal health. The Mediterranean diet (MedDiet) is the traditional healthy dietary pattern of people living in countries bordering the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%